A case report: management of hypernatremia in diabetic ketoacidosis patient with type II diabetes mellitus - Pratikto, Bella Christie; Suryana, Ketut (International Journal of Research in Medical Sciences, 2023)
Diabetic ketoacidosis (DKA) is a life-threatening hyperglycemic crisis. DKA rarely presents with hypernatremia, so it is not a common case. We report an unusual case of a 47-year-old woman with type 2 diabetes mellitus (T2DM) admitted with blood glucose 654 milligrams/deciliter and serum sodium 147 millimoles/liter. Patient was transferred to ICU for further management. Patient was given initial bolus of normal saline and switched to D5-1/4 saline for correction of hypernatremia along with insulin therapy. The patient gradually recovered. This report reminds us about how we choose the right treatment to correct the hypernatremia in patient with DKA and also reminds that monitoring the electrolyte levels in hyperglycemia is relevant in the management of diabetes.